The Incidence of Flatfoot amongst Athletes in Port-Harcourt (Journal of Experimental and Clinical Anatomy, 2004)
The incidence of flat foot amongst 200 athletes in Port Harcourt was determined using the contact 11 index development by Qamara. The athletes were drawn from various sports clubs in Port Harcourt town. The mean and standard deviation of contact index 11 were determined, and the degree of flat foot graded as either probable (Mean + 1SD to 2SD) or definite (Mean + 3SD or more). Incidence of definite unilateral flat foot was found to be 3% (males) and 4% (females). The incidence of bilateral flat foot was found to be 7% (Males) and 8% (Females).